Numerical Analysis of the Influences of Geometrical Deviation on Delamination in Composite Laminates around the Countersunk Hole - Xueshu Liu; Yuxing Yang; Li Huang; Ping Zhang; Hang Gao (International Journal of Aerospace Engineering)
During countersunk hole machining, defects like geometrical deviation of the chamfer angle and delamination are easily introduced into the structure. To investigate the influences of geometrical deviation on delamination propagation around the countersunk hole during assembly, a progressive damage model (PDM) combining cohesive element was proposed and validated. Numerical analyses were then carried out to study delamination propagation behavior under the influences of geometrical parameters including delamination factor, chamfer angle, and location of delamination. The results show that when delamination appears at the transition area of the countersunk hole, the load causing the delamination evolution is much smaller than other cases.